Bosworth, 1485 the battle that transformed England - Jones, Michael 1940- (Pegasus, 2015)
Argues that Richard III's defeat at Bosworth Field was not inevitable using new archival discoveries to reveal new details about the battle and Henry Tudor's reliance on French mercenaries